THE ROLE OF HUMAN RESOURCE MANAGEMENT (HRIS) INTEGRATION AND HR SYSTEM DIGITALIZATION IN IMPROVING THE QUALITY OF EMPLOYEE TRAINING AND DEVELOPMENT - La Saudin; Adrian Polim (Yayasan Education and Social Center, 2026)
This study aims to analyze the role of Human Resource Information System (HRIS) integration and HR system digitalization in improving the quality of employee training and development at the Batui and Luwuk Selatan District Offices, Banggai Regency. The approach used was qualitative with data collection techniques through in-depth interviews, observation, and documentation. Data analysis was conducted using NVivo to identify key themes related to HRIS implementation, HR digitalization, and the quality of employee training. The results show that HRIS implementation is still limited to basic administrative functions and has not been optimally integrated into the HR decision-making system. HR digitalization is still in its early stages with limited digital literacy among civil servants and uneven distribution of supporting infrastructure. The quality of employee training is not fully based on competency needs analysis, making it less effective in improving employee performance. This study concludes that HRIS integration and HR digitalization play an important role in improving the effectiveness of employee training and development, but still face various challenges in its implementation. System strengthening, increasing digital competence of civil servants, and optimizing the use of HR data are needed to support more effective decision-making within the sub-district government environment